Sustainable vehicles for decarbonizing the transport sector : A comparison of biofuel, electric, fuel cell and solar-powered vehicles - Reddy, Vennapusa Jagadeeswara; Hariram, Nediyirippil Prakasan; Maity, Rittick; Mohd Fairusham, Ghazali; Sudhakar, Kumarasamy (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Climate change necessitates urgent action to decarbonize the transport sector. Sustainable vehicles represent crucial alternatives to traditional combustion engines. This study comprehensively compares four prominent sustainable vehicle technologies: biofuel-powered vehicles (BPVs), fuel cell vehicles (FCVs), electric vehicles (EVs), and solar vehicles. We examine each technology’s history, development, classification, key components, and operational principles. Furthermore, we assess their sustainability through technical factors, environmental impacts, cost considerations, and policy dimensions. Moreover, the discussion section addresses the challenges and opportunities associated with each technology and assesses their social impact, including public perception and adoption. Each technology offers promise for sustainable transportation but faces unique challenges. Policymakers, industry stakeholders, and researchers must collaborate to address these challenges and accelerate the transition toward a decarbonized transport future. Potential future research areas are identified to guide advancements in sustainable vehicle technologies.